Mobile And Cloud Computing Based It Strategic Planning (Case Study: Primeone School Medan) - Miharja, Satriya (STMIK TIME, 2020)
PrimeOne is one of the national school in Medan which has used IT application in its operational, however the IT applied hasn’t reached the maximum standard and caused the important information couldn’t be accessed personally by parents such as checking for the tuition fee paid, checking for the students study progress, etc. So that it might cause some parents object to send their kids to PrimeOne School. This shows that PrimeOne School needs to have good IT Strategic Planning so that the school can serve the best for parents and reach the operational goals effectively. There are some purposes in this research (1) Plan for the good IT Strategic Planning which gets along well with school vision, mission, goals and business process for the next 2 years, which is 2016-2017 period, (2) To gain the Information System and Information Technology solution also recommendation which can support school business strategy to increase the interest of parents and school competition. This research used several methods to analyze which are SWOT analysis, Potter Five Forces Analysis, CSF Analysis and Value Chain Analysis. From these analysis, information system strategy, information technology strategy and IS/IT management strategy are produced. The result of this research is a recommendation or suggestion which is portfolio application which can be used for PrimeOne. The conclusion from this research is PrimeOne School is at the Second Quadran where it is expected to enlarge the IS/IT strategy applied and produce IS/IT strategy suggestion ( Promotion Application with Social Media Cloud Computing, POS Mobile Application, Interactive Learning Application, Facility Application and develop network connection between the school buildings ) which will increase parents’ interest and school competition.